Preparação e caracterização de Blendas à base de Lignina Kraft Oxipropilada e Amido - Oliveira, Priscila Barbosa de (2021)
The implementation and development of biorefinery processes is of great importance and constitutes the basis for the establishment of an economy based on bioresources. In this context, studies aiming at the use of waste generated in industries are being carried out. The present work describes the production and characterization of blends of corn starch and powdered Kraft lignin, derived from the production process of eucalyptus pulp by the company Suzano S.A, oxypropylated, and evaluation of their possible application. Initially, the oxypropylation of Kraft lignin was carried out, through a reaction with propylene oxide and potassium hydroxide in a Par Reactor, where the product of the reactions (oxypropylated lignin - OP4) was used for the preparation of blends of blends with corn starch in natura, in different proportions and temperatures, MAN1: 1:1 to 60°C, MAN2: 1:1 to 120°C, MAN3: 2:1 to 120°C. From SEM tests, it was possible to verify the need for gelatinization of starch in order to obtain homogeneous mixtures free of granules. After the starch was gelatinized (PURE AG), the mixtures were made again with OP4, this time, obtaining the blends in homogeneous mixtures (MAG1, MAG2, MAG3). The characterization of the inputs used and the mixtures obtained was done by infrared spectroscopy (FTIR), to assess their chemical composition, by thermal analysis (TGA and DSC) to assess their thermal stability and other transitions, by microscopy (MEV) for morphological evaluation , by moisture absorption tests to assess their absorbent properties, by contact angle measurements to assess the surface energies of the materials obtained, and by solubility tests. To make the wires, glass Pasteur pipettes were used as molds, and later they were fired in two steps, firstly, stabilization at a temperature of 250ºC for 1h, and carbonization under an inert atmosphere at a temperature of 900ºC for 10h. It was found that the blends produced presented a polar molecular characteristic. It was also verified that the products resulting from the thermal processes of the threads resulted in carbon fibers with low mechanical resistance, as they became fragile and brittle. Another point observed was the presence of pores in the structures of blends and threads, after carbonization. The amount and size of pores can be related to the proportion of oxypropylated lignin used, with the greater the mass of OP4, the greater the amount of pores. It was found that the materials produced cannot be used for carbon fiber applications, but have potential for use in other applications, such as catalyst and/or adsorbent materials.